2005
DOI: 10.1007/s00018-005-4478-8
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 19 processes the laminin 5 gamma 2 chain and induces epithelial cell migration

Abstract: In this study we analyzed the proteolytic activity of MMP-19 and its impact on keratinocyte migration. In the HaCaT keratinocyte cell line overexpressing wild-type MMP-19 (HaCaT-WT), transmigration through fibrin and type IV collagen matrices was significantly increased compared to cells harboring a catalytically inactive mutant (HaCaT-EA). Studying the expression of MMP-19 in early stages of squamous cell cancer (SCC), we found co-localization of MMP-19 and laminin 5 at the invading tumor front but not in sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
57
0
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 44 publications
2
57
0
4
Order By: Relevance
“…42 MMP-19 was widely expressed by keratinocytes at the basal epidermal layer of keratoacanthomas and sporadically in 40% of the SCCs. We and others have previously reported that MMP-19 is absent from invasive cancer cell nests of well-differentiated SCC, 14,34 and our new findings support these results. Thus, the loss of MMP-19 from basal epithelial cells of keratoacanthomas might serve as a warning sign of cancer development.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…42 MMP-19 was widely expressed by keratinocytes at the basal epidermal layer of keratoacanthomas and sporadically in 40% of the SCCs. We and others have previously reported that MMP-19 is absent from invasive cancer cell nests of well-differentiated SCC, 14,34 and our new findings support these results. Thus, the loss of MMP-19 from basal epithelial cells of keratoacanthomas might serve as a warning sign of cancer development.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in an epithelial carcinogenesis model of HPV16/MMP-9À/À mice, MMP-7 and MMP-13 are only seen in frank carcinoma 33 and in tumors both have been detected exclusively in malignantly transformed squamous cell carcinoma cells but not in premalignant lesions. 34 MMP-7 contributes to the initiation of epithelial-to-mesenchymal transition by cleavage of E-cadherin. 33,35 In keratoacanthomas, MMP-7 protein was not generally expressed in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The catalytic domain of MMP19 degrades various ECM components including collagen type IV, nidogen-1, fibronectin, tenascin-C isoform, aggrecan, and laminin-5-gamma-2-chain. [7][8][9] The catalytic domain contains the typical zinc-binding motif; the zinc and calcium ions additional to this domain are necessary for structure stability and enzymatic activities of MMPs. 10 The glutamate residue at the zinc binding motif activates the zinc-bound water molecule to provide the nucleophile during cleaving activities on peptide bonds.…”
mentioning
confidence: 99%
“…Furthermore, the 80-kDa ␥2x form has been associated with tissues undergoing remodeling, whereas full-length ␥2 is found in quiescent tissues (13)(14)(15)(16). Other MMPs, including MMP-3, -12, -13, -14, -19, and -20, have also been shown to cleave the ␥2 chain, generating the ␥2x fragment, inducing epithelial cell migration (15,17,18). In addition to this cleavage site near the coiled-coil region, MMP-14 cleaves the short arm of the ␥2 chain at an additional site (15,19), releasing an ϳ20-kDa D3 domain fragment containing three EGF repeats.…”
mentioning
confidence: 99%